Pengembangan Mekanisme Monitoring Termin Kontrak Menggunakan Pendekatan RCPS untuk Pengendalian Proyek dan Manajemen Kontrak di Direktorat Enjiniring PLN Enjiniring - Tumewu, Dewi; Desiawan, Victor Assani (Jurnal Teknik Sipil Terapan (JTST), 2025)
Effective monitoring of contractual milestones (termin) is essential in project and construction management because milestone validation directly influences schedule control, cost performance, and revenue recognition. In PLN Enjiniring, the existing monitoring process remains fragmented, spreadsheet-based, and weakly integrated with engineering progress, leading to inconsistent data, unreliable milestone verification, delays in billing, and deviations from planned performance. This study employs a process engineering approach supported by Root Cause Problem Solving (RCPS) to analyze systemic deficiencies, quantify their impact on construction project control, and redesign a standardized monitoring mechanism. The redesigned model introduces unified milestone indicators, integrated technical–administrative control points, and a structured verification workflow. A dashboard prototype was developed to provide real-time visualization of milestone status, deviation analysis, and revenue projections. Pilot testing across several engineering service contracts demonstrated improvements in milestone accuracy (25–30%), reduced inter-unit discrepancies (up to 30%), faster update cycles, and a 50–70% reduction in revenue reconciliation time. These findings indicate that a systematically analyzed and structured monitoring mechanism strengthens construction project control, improves schedule and cost reliability, and enhances the PMO's strategic role in engineering-based project environments.